AB0385 Tofacitinib in Rheumatoid Arthritis: Results of Post-Approval Investigator Initiated Trial. (15th July 2016) - Karateev, D.; Luchikhina, E.; Abdulganieva, D.; Lapshina, S.; Baranov, A.; Lapkina, N.; Petrov, D.; Ivanova, O.; Salnikova, T.; Sorotskaya, V.; Semagina, O.; Mazurov, V.; et al.
Abstract : Background: Tofacitinib (TOFA) was approved in Russia for treatment of patients with rheumatoid arthritis (RA) in 2013, but published information about its post-approval use limited to some individual clinical observations. Objectives: To study the efficacy and safety of TOFA in patients with severe active RA in clinical practice. Methods: We present the preliminary results of ongoing investigator initiated study "Local open label multicenter observational study of efficacy and safety of Tofacitinib in patients with active rheumatoid arthritis with insufficient response to DMARDs", a part of a research program "Russian investigation of methotrexate and biologics in early active inflammatory arthritis" (REMARCA). We included 120 patients (pts) with severe active RA (97 females, 23 males), with median age 51, 0 [41, 25; 59, 0] years and disease duration 60, 0 [24, 25; 120, 0] months, 92 (76, 7%) RF positive, 91 (75, 8%) ACPA positive, who were non-responders to methotrexate (MTX) at least 15 mg/week and/or other synthetic DMARDs, and biological DMARDs (b-DMARDs). 9 of 30 b-DMARDs non-responders had 2–4 biologics in history. Tuberculin test and chest X-ray were performed in all pts before TOFA prescription. We use TOFA in all the pts in starting dose 5 mg BID per os with possibility to increase the dose to 10 mg BID if needed. The use of TOFA in combination or as monotherapy was a prerogative of the rheumatologist. By January 2016, 91 patients received TOFA for 3 months and 55 pts – for 6 months. Results: TOFA used in combination with MTX in 84 (70%) pts, with Leflunomide in 12 (10%), as monotherapy – in 24 (20%) pts. Dose escalation to 10 mg BID was carried out in 25 (20, 8%) pts. Results presented in the table . 20 episodes of adverse events (AEs) in 14 pts observed: liver test 2-fold elevation – 4 cases, Herpes simplex – 3, skin rash – 2, erysipelas – 1, Herpes zoster – 1, latent TB activation – 1, bronchitis – 1, nasopharyngitis – 1, cystitis – 1, hemorrhoids – 1, headache – 1, nausea – 1. No serious AEs were reported. TOFA has been withdrawn in 4 pts: three due to lack of efficacy, one due to allergic skin rash. Conclusions: TOFA was effective in clinical practice for control of disease activity in patients with severe RA with multiple resistance to synthetic and biological DMARDs during short-term follow up. Safety was satisfactory; there were no cases of serious AEs. Acknowledgement: Trial State registration number: 01201454666 (http://www.rosrid.ru/search ). This scientific study was supported by Pfizer educational grant. Disclosure of Interest: None declared